FOREIGN LANGUAGE LEARNING: EXPLORING THE STRUGGLES OF FILIPINO STUDENTS IN LEARNING THE SPANISH LANGUAGE - M. Parayno, Milcah (LP2M Universitas Bina Mandiri Gorontalo, 2023)
Learning and knowing a foreign language has become an advantage and a valuable skill, particularly for students seeking more job opportunities after graduation. The Spanish language, which is the fourth most spoken language in the world, is a popular foreign language for students to learn. However, studies have demonstrated that learning Spanish offers significant struggles to learners from varied backgrounds and that there is a need to identify these individual challenges in order to improve the teaching and learning of Spanish. Thus, this study highlighted the challenges that Filipino students faced in learning Spanish and proposed potential solutions to overcome those difficulties and limitations. The researchers utilized the qualitative research method, specifically the descriptive phenomenological type, and used thematic analysis to analyze the data gathered from 10 participants who are learning Basic and Advanced Spanish as a foreign language. The findings of the study revealed that students struggle with the four domains of language: syntax, semantics, morphology, and phonology. Low motivation due to the perceived irrelevance of Spanish to their major, limited opportunities to practice the language, as well as lack of teacher engagement in the course also adds to their struggles. In addition, the results showed that students try to overcome these challenges by exploring opportunities for target language exposure, utilizing self-learning methods, using online translation software applications, and collaborating with peers